Hello,
It's me again! This is a buck with input filter. The question I have is how to determine the inductor ripple current of L2.
To summarize my work with voltsec balance and ampsec balance:
1. Voltsec balance for L1 > 0 = Vg  VC1, so VC1 = Vg
2. Voltsec balance for L2 > 0 = VC1*D  V, so V = VC1 * D and since VC1 = Vg from #1, then V = Vg * D
3. Ampsec balance for C1 > 0 = IL1  IL2 * D
3a. IL1 = IL2 * D is the DC component of IL1
4. Ampsec balance for C2 > 0 = IL2  V/R
4a. IL2 = V/R is the DC component of IL2
4b. Since V = Vg * D, then IL2 = (Vg * D)/R
And since IL1 = IL2 * D, and IL2 = (Vg * D)/R, then finally:
IL1 = (D^2 * Vg) / R
All those are correct, and I have attached my work.
Here is the issue. From an ideal buck converter with no input filter, the inductor ripple current is ((Vg  V) * D * Ts) / (2 * L). This should be the same for L2 in the above circuit. If VC1 = Vg then I would calculate the inductor ripple in L2 as:
Eq. 1 : ((Vg  V) * D * Ts) / (2 * L2)
It's the same as before! But this answer is wrong. The correct answer is:
e
Eq. 2 : (Vg * D * Ts) / (2 * L2)
I do not see how we get from Eq1 to Eq2. Why/How does the output voltage drop out?
It's me again! This is a buck with input filter. The question I have is how to determine the inductor ripple current of L2.
To summarize my work with voltsec balance and ampsec balance:
1. Voltsec balance for L1 > 0 = Vg  VC1, so VC1 = Vg
2. Voltsec balance for L2 > 0 = VC1*D  V, so V = VC1 * D and since VC1 = Vg from #1, then V = Vg * D
3. Ampsec balance for C1 > 0 = IL1  IL2 * D
3a. IL1 = IL2 * D is the DC component of IL1
4. Ampsec balance for C2 > 0 = IL2  V/R
4a. IL2 = V/R is the DC component of IL2
4b. Since V = Vg * D, then IL2 = (Vg * D)/R
And since IL1 = IL2 * D, and IL2 = (Vg * D)/R, then finally:
IL1 = (D^2 * Vg) / R
All those are correct, and I have attached my work.
Here is the issue. From an ideal buck converter with no input filter, the inductor ripple current is ((Vg  V) * D * Ts) / (2 * L). This should be the same for L2 in the above circuit. If VC1 = Vg then I would calculate the inductor ripple in L2 as:
Eq. 1 : ((Vg  V) * D * Ts) / (2 * L2)
It's the same as before! But this answer is wrong. The correct answer is:
e
Eq. 2 : (Vg * D * Ts) / (2 * L2)
I do not see how we get from Eq1 to Eq2. Why/How does the output voltage drop out?
Attachments

224.6 KB Views: 67

261.5 KB Views: 58